PRODUCTION OF BLACK MASTIC SEEDLINGS (Myracrodruon urundeuva Freire Allemao) USING ALTERNATIVE SUBSTRATES - Azevedo, Genesis Alves de [UNESP]; Azevedo, James Ribeiro de (Faema-fac Educacao & Meio Ambiente, 2023)
The use of organic waste as an alternative substrate is a viable alternative, since they are rich in nutrients and produced in large quantities. The objective of this work was to evaluate the efficiency of using sewage sludge and carbonized rice husks as an alternative substrate in the production of pepper tree seedlings (Myracrodruon urundeuva Freire Allemao). The experiment was conducted in a protected environment at the Faculty of Engineering/UNESP, Ilha Solteira Campus. A completely randomized design was used, with twenty treatments and six replications, totaling 120 seedlings. The proportions of sewage sludge (LE) and carbonized rice husks (CAC) were tested: (100%LE, 0%CAC), (80%LE, 20%CAC), (60%LE, 40%CAC), (40%LE, 60%CAC), (20%LE, 80%CAC) and (100% Commercial substrate). Plant height, diameter, root length and volume, number of leaves, fresh and dry root mass, fresh and dry aerial mass, percentage of germination were evaluated. The aroeira-preta seedlings produced with LE and CAC showed lower growth than the results presented by the control with commercial substrate. It is recommended the use of LE and CAC in proportions equivalent to 40% of sewage sludge and 60% of carbonized rice husks, as they present higher biometric averages for the seedlings.
Keywords: Biosolids; Waste; Biometry; Forest Species